50, 000 years of archaeological site stratigraphy and micromorphology in Boodie Cave, Barrow Island, Western Australia. (October 2017) - Ward, I.; Veth, P.; Prossor, L.; Denham, T.; Ditchfield, K.; Manne, T.; Kendrick, P.; Byrne, C.; Hook, F.; Troitzsch, U.
Abstract: This study explores the application of soil micromorphological and automated scanning electron microscopy mineralogical analysis to characterise lithological boundaries and site formation history from an archaeological cave site on Barrow Island, northwestern Australia. The high-resolution characterisation is used to document the changing depositional context within Boodie Cave from the earliest period of occupation around 50 ky BP through to when transgressing seas isolated the island around 7 ky BP. Comparisons are made between excavations at the front of the cave — where stratigraphic integrity is high and a thicker, more comprehensive early Holocene sequence is preserved, with excavations inside the cave — where stratigraphic integrity is lower but an older Pleistocene record is preserved. The combination of these depositional scenarios provides a complete stratigraphic sequence for Boodie Cave, with depositional contacts defined at macro-, meso- and micro-scale levels. These contacts include erosive surfaces and trampled (ground) surfaces, such as the upper interface of SU5 and SU4. Based on the mineralogical and textural variations (microfacies) preserved within each unit, the vertical mixing zone is estimated to be between 1 and 5 cm. This reworking has not affected the general sequence of sedimentological (including grain size and mineralogy) and macro-cultural changes, which record an increasingly marine-dominated assemblage as the coastline encroaches. The integration of microscopic observations with anthracological, archaeomalacological, zooarchaeological and lithic analyses provides a more dynamic and comprehensive dialogue for interpreting the formation history of Boodie Cave and likely other early occupation sites from northern Australia. Highlights: A multi-scalar analysis of a 50, 000 year archaeological record from Barrow Is. is presented. High-resolution analysis includes macromicromorphological and automated mineralogical analysis. Results integrate anthracological, zooarchaeological, shell and lithic analyses.